STRATEGI PEMBELAJARAN KOSAKATA ABSTRAK UNTUKMENINGKATKAN KEMAMPUAN BERBAHASA ANAK TUNARUNGU USIADINI - ., Hermanto (MAJALAH ILMIAH PEMBELAJARAN, 2012)
Language is a key element in the communication, the basis for a person toexpress, and development of a variety of information or knowledge.Through the language used, one can know the depth of knowledge andeven their way of thinking. For normal children, the development oflanguage or vocabulary will grow more rapidly through the five senses arerelatively natural. They vocabulary develop through observation, listening,touch, foretaste, and sense of smell. In contrast to children with hearingimpairment, they can not acquire vocabulary naturally due to the loss ofauditory function. For minimize losses due to the loss of the sense ofhearing, the necessary learning strategies to facilitate the acquisition ofvocabulary to children with hearing impairment. Learning strategies thatinclude using a variety of media to be more real and visual or more will betaught as a vocabulary with the help of colors and symbols, using longstrides in instilling the concept first, and use mapping concept.